Patologia do Coração na AIDS. Estudo de 73 Necropsias Consecutivas - Okoshi, Marina Politi [UNESP] (My University, 1996)
Purpose - To study the incidence and the etiology of the cardiac lesions in AIDS patients. Methods - The autopsy protocols and the filled slides of the heart from 73 consecutive AIDS patients were reviewed. There were, at least, 2 slides of each heart stained by haematoxylin-eosin; when indicated, Ziehl-Nielsen, Gram and Gomori Grocott stains were used. Results - No cause of death was assigned to the heart. There was involvement of the heart in 66 (90%) cases. Marked atrophy of cardiac fibers with or without lipomatosis was observed in 38 patients. Interstitial infiltrates of myocardium were present in 38 necropsies and in 13 of these cases a probable pathogen was demonstrated: cryptococcus neoforms in three cases and mycobacteria tuberculosis, atypical mycobacteria, toxoplasma gondii, trypanosoma cruzi and cytomegalovirus in two cases each. Bacterial endocarditis was found in 4 autopsies and Kaposi sarcome in one. The pericardium was involved in 22 cases; in 12 there was only non specific mononuclear infiltration. Conclusion - Autopsy examination of the heart from AIDS patients revealed frequent pathologic involvement.
Pathology of the Heart in AIDS. A Study of 73 Consecutive Necropsies
Keywords: Acquired immune deficiency syndrome; Autopsy; Cardiac lesions